Analisis Kesalahan Berbahasa Dalam Artikel Yang Berjudul "Meningkatkan Budaya Literasi Membaca dan Menulis Siswa Melalui Pembiasaan di Kelas" - Ratna Lolane Sianipar; Stela Parta Siagian; Stevani Br Situmorang; Jesicha Nainggolan; Erfanintiya Siringoringo; Mustika Wati Siregar (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to identify and analyze language errors at the syntactic level in the article entitled "Improving the Literacy Culture of Reading and Writing Through Students' Habituation in the Classroom." The focus of the research is on errors in sentence structure, punctuation, and other syntactic issues that may hinder effective communication in academic writing. This study employs a qualitative approach with a descriptive method, aimed at providing a systematic, factual, and accurate description of a particular object. The data collection technique used in this research is reading and recording techniques, where the article is analyzed thoroughly to identify any linguistic mistakes. The findings of the study revealed several types of errors in the analyzed article, including spelling errors, improper use of punctuation, ineffective sentence structures, mischoices of words (diction), and inconsistencies in language usage. These errors affect the clarity and professionalism of the article. Based on these findings, this study emphasizes the importance of understanding and applying the Indonesian language rules as outlined in the General Guidelines for Indonesian Spelling (PUEBI). By adhering to these guidelines, writers can improve their writing skills, making their academic papers more effective, clear, and in accordance with established language norms. This research contributes to enhancing the quality of academic writing by highlighting areas where language proficiency is crucial in conveying ideas clearly and accurately.